Ozone-Induced Aryl Hydrocarbon Receptor Activation Controls Lung Inflammation via Interleukin-22 Modulation - Michaudel, Chloé; Bataille, Florent; Maillet, Isabelle; Fauconnier, Louis; Colas, Cyril; Sokol, Harry; Straube, Marjolène; Couturier-Maillard, Aurélie; Dumoutier, Laure; van Snick, Jacques; Quesniaux, Valérie F.; Togbe, Dieudonnée; et al. (Frontiers in Immunology, 2020)
Airborne ozone exposure causes severe lung injury and inflammation. The aryl hydrocarbon Receptor (AhR) (1), activated in pollutant-induced inflammation, is critical for cytokine production, especially IL-22 and IL-17A. The role of AhR in ozone-induced lung inflammation is unknown. We report here that chronic ozone exposure activates AhR with increased tryptophan and lipoxin A4 production in mice. AhR−/− mice show increased lung inflammation, airway hyperresponsiveness, and tissue remodeling with an increased recruitment of IL-17A and IL-22-expressing cells in comparison to control mice. IL-17A- and IL-22-neutralizing antibodies attenuate lung inflammation in AhR−/− and control mice. Enhanced lung inflammation and recruitment of ILC3, ILC2, and T cells were observed after T cell-specific AhR depletion using the AhRCD4cre-deficient mice. Together, the data demonstrate that ozone exposure activates AhR, which controls lung inflammation, airway hyperresponsiveness, and tissue remodeling via the reduction of IL-22 expression.